Spatial Soundscapes and Virtual Worlds: Challenges and Opportunities - Rajguru, Chinmay; Obrist, Marianna; Memoli, Gianluca (Frontiers in Psychology, 2020)
There is a growing effort to characterise the soundscapes around us to design more compelling and immersive experiences. This review paper focuses on the challenges and opportunities around sound perception with the particular angle on spatial sound perception in a virtual reality (VR) cityscape. We review how research on the temporal aspects have recently been extended towards the evaluation of the spatial factors when designing soundscapes. In particular, we canvass some key findings addressing the human capability of localizing and distinguishing spatial sound cues in light of different technical setups. We highlight those studies carried out in both a real world and virtual reality setting to evaluate spatial sound perception. We conclude this review highlighting the opportunities offered by VR technology and the remaining open questions for virtual soundscape designers, especially in light of increased advances in spatial sound stimulation.